Analisis Break Even Point Dan Marginal Kontribusi Pada UMKM Sabana Outlet Karangsari Kabupaten Bekasi - Purwati .; Senja Aulya (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study was conducted to analyze profit planning at UMKM Sabana Outlet Karangsari, Regency Bekasi, through the Break Even Point (BEP) and contribution margin approaches. UMKM plays a vital role in Indonesia's economy, including in the fast food sector such as Sabana Fried Chicken. This research uses a quantitative descriptive method with data collection techniques including field observation, interviews, and financial documentation. The results show that the total fixed monthly costs amount to IDR 16,375,000 and variable costs are IDR 6,600,000. With a selling price per unit of IDR 10,000 and variable cost per unit of IDR 7,333, the contribution margin per unit is recorded at IDR 2,667. Based on calculations, the break-even point is reached at sales of 6,139 pieces or equivalent to revenue of IDR 61,390,000. If the daily sales target is 30 pieces, the BEP can be achieved in approximately 205 days. These results indicate that BEP and contribution margin analyses are effective tools to support decision-making in improving efficiency, planning profit strategies, and ensuring the sustainability of UMKM operations, especially amid economic challenges and increasingly competitive markets. By applying profit planning based on quantitative analysis, business actors can map strategic steps more accurately, adaptively, and with a long-term growth orientation.